How to Become an Obstetric Authority? Demarcation Dispute between Midwives and Doctors in German Midwifery Manuals from the Early Modern Period (Theatrum historiae, 2020)
The subject of the study is the analysis of early modern midwifery manuals from German-speaking regions written in the period between the second half of the seventeenth century and the first half of the eighteenth century. This period can be described as the beginning of the so-called demarcation dispute between the midwives and obstetricians. A characteristic manifestation of the dispute was an enormous production of midwifery manuals written by physicians and surgeons. At the same time, three German midwives (Justina Siegemund, Anna Elisabeth Horenburg and Barbara Wiedemann) published their treatises on childbirth. The aim of the study is to show the legitimation and self-presentation strategies used by the female and male authors of the midwifery manuals in order to integrate themselves into obstetric authorities. Moreover, the study focuses on the differences between the approach of female and male authors to midwifery.
Keywords: midwife; demarcation dispute; Early Modern Period; Obstetrics; Authority; Strategy